Studi Komparatif Penentuan Arah Kiblat Menggunakan Rubu' Mujayyab Dan Kompas Easy Qiblat 3 In 1 pada Handphone Android - Sapri Ali (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
The author is interested in comparing the easy qibla 3 in 1 compass with one of the classic tools, namely the rubu 'mujayyab which both have weaknesses and strengths. In this study, the issue discussed is how is the accuracy level of determining the Qibla direction using the rubu 'mujayyab and the 3 in 1 easy qibla compass on an android phone? The type of research used by this author is classified as qualitative, descriptive comparative (comparative approach), which aims to better understand the rubu mujayyad and compass easy qibla 3 in 1 on mobile phones and compare them in terms of their weaknesses and strengths. where the primary data is data obtained directly from observations, the book of Durussul Falakiyyah and the Easy Qibla 3 in 1 compass. The findings from this research are that when the practice of measuring the Qibla is not the same, there is a difference of about 0˚ 8′ 52.42ʺ which if made in meters from the east to west line distance which is both 9 meters produces a difference of about 0.03 meters . According to the author, this is still within reasonable limits or allowed deviation categories. maybe this is due in part to the advantages and disadvantages of each of the two tools. The advantages of the Easy Qibla 3 in 1 compass, such as how to use it is relatively easy, still functions in all kinds of weather and conditions, easy to use for ordinary people or not especially astronomers, easy to carry everywhere.